Parenteral Nutrition Is One of the Most Significant Risk Factors for Nosocomial Infections in a Pediatric Cardiac Intensive Care Unit. (29th November 2015) - Netto, Roberta; Mondini, Matteo; Pezzella, Chiara; Romani, Lorenza; Lucignano, Barbara; Pansani, Laura; D'argenio, Patrizia; Cogo, Paola
Abstract : Background: Nosocomial infections (NIs) are associated with significant morbidity and mortality and increased healthcare costs. We aimed to assess the NI epidemiology and associated risk factors in a pediatric cardiac intensive care unit (PCICU). Materials and Methods: Prospective observational study on 1106 patients admitted to a PCICU from January 1, 2012, to October 31, 2013. NIs were defined and recorded weekly by a multidisciplinary team. Independent risk factors for NIs were assessed by logistic regression analysis in the overall cohort, in cardiac surgical patients, and in those who had cardiopulmonary bypass (CPB). Results: Ninety‐two patients (8.3%) had NIs. Overall mortality was 2% but 8.3% in children with NIs ( P < .001). The most frequent NIs were pneumonia (19.6%), bacteremia of unknown origin (16.3%), and catheter‐associated bloodstream infection (14.1%) caused mainly by Staphylococcus aureus and Pseudomonas aeruginosa . In the overall cohort, independent risk factors for NIs were number of days of parenteral nutrition (PN), days of invasive and noninvasive ventilation, ward before PCICU admission, and days of PCICU stay; in the cardiac surgical patients, the risk factors were days of PN and days of invasive and noninvasive ventilation; in children who had undergone CPB, the risk factors for NIs were days of PN, delayed sternal closure, reintervention, length of CPB, younger age, and days of invasive ventilation. Conclusion: Mortality was significantly higher in patients with NIs. The use of PN was one of the most significant predictors for NIs in the overall cohort of PCICU patients, cardiac surgical patients, and those who required CPB.